2014
DOI: 10.4274/npa.y6510
|View full text |Cite
|
Sign up to set email alerts
|

Endüstriyel Bir Patlama Sonrasında Akut Stres Bozukluğu ve Travma Sonrası Stres Bozukluğu Gelişiminde Olası Risk Faktörleri

Abstract: Introduction: There have been deaths and injuries after an explosion which happened in an industrial region in Ankara in February 2011. The aim of this study was to determine the prevalence of acute stress disorder (ASD) and posttraumatic stress disorder (PTSD), and to determine the variables which can be the risk factors for PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A study examining the development of PTSD after an industrial explosion in Turkey reported that factors such as having any other mental disorder, being familiar with people among the deceased or injured, experiencing physical harm, and seeing bodies of deceased were reported as risk factors for PTSD (Taymur et al 2014).…”
Section: ) Systematic Desensitizationmentioning
confidence: 99%
“…A study examining the development of PTSD after an industrial explosion in Turkey reported that factors such as having any other mental disorder, being familiar with people among the deceased or injured, experiencing physical harm, and seeing bodies of deceased were reported as risk factors for PTSD (Taymur et al 2014).…”
Section: ) Systematic Desensitizationmentioning
confidence: 99%
“…Similarly, Taymur et al in a prospective study on 197 victims of an industrial explosion in Ankara, revealed that; 1 month after the explosion, 37.1% of the survivors suffered from acute stress disorder, and 40% developed PTSD, while 8.9% of subjects who witnessed the event from afar (through the shake, visual, and auditory effects) developed PTSD. [7] Of interest, in a study surveying 438 participants, Raker et al reported that less than 1 year after Hurricane Katrina, 43.8% of the victims suffered from PTSD. Even though this number has been decreasing, 1 in 6 survivors (16.7%) still experienced post-traumatic symptoms twelve years after the storm.…”
Section: Introductionmentioning
confidence: 99%